Characterization of the tribologically relevant cover layers formed on copper in oxygen and oxygen-free conditions - Selina Raumel; Khemais Barienti; Hoang-Thien Luu; Nina Merkert; Folke Dencker; Florian Nürnberger; Hans Jürgen Maier; Marc Christopher Wurz (Friction)
Abstract Engineering in vacuum or under a protective atmosphere permits the production of materials, wherever the absence of oxygen is an essential demand for a successful processing. However, very few studies have provided quantitative evidence of the effect of oxidized surfaces to tribological properties. In the current study on 99.99% pure copper, it is revealed that tribo-oxidation and the resulting increased abrasive wear can be suppressed by processing in an extreme high vacuum (XHV) adequate environment. The XHV adequate atmosphere was realized by using a silane-doped shielding gas (1.5 vol% SiH4 in argon). To analyse the influence of the ambient atmosphere on the tribological and mechanical properties, a ball—disk tribometer and a nanoindenter were used in air, argon, and silane-doped argon atmosphere for temperatures up to 800 °C. Resistance measurements of the resulting coatings were carried out. To characterize the microstructures and the chemical compositions of the samples, the scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) were used. The investigations have revealed a formation of η-Cu3Si in silane-doped atmosphere at 300 °C, as well as various intermediate stages of copper silicides. At temperatures above 300 °C, the formation of γ-Cu5Si were detected. The formation was linked to an increase in hardness from 1.95 to 5.44 GPa, while the Young’s modulus increased by 46% to 178 GPa, with the significant reduction of the wear volume by a factor of 4.5 and the suppression of further oxidation and susceptibility of chemical wear. In addition, the relevant diffusion processes were identified using molecular dynamics (MD) simulations.